TRIPLE SYNCHRONOUS TUMORS PRESENTING AS RIGHT NASOLABIAL BASAL CELL CARCINOMA, PAPILLARY THYROID CARCINOMA AND PROLACTINOMA: A RARE CASE REPORT - III, Te MC; DB, Lumanlan-Mosqueda; KJ, Demegillo (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION A 57-year-old female presented with triple synchronous tumors with a rare combination of basal cell carcinoma (BCC) of the right nasolabial area, papillary thyroid carcinoma (PTC) and prolactinoma. The case initially presented a diagnostic dilemma in approaching multiple tumors from different endocrine organs. On work up, serum prolactin was elevated and an enhancing thyroid mass on neck CT scan and a pituitary mass on cranial MRI were noted. Bromocriptine was given and she underwent total thyroidectomy and wide excision of the right nasolabial BCC. On follow up, repeat serum prolactin decreased back to normal from baseline. This case report aims to provide an organized approach to multiple tumors involving endocrine organs and to reconcile the challenge in ruling out metastasis and syndromic disorders such as Multiple Endocrine Neoplasia. This paper also aims to highlight the need for a multidisciplinary team in the management of multiple tumors. CASE After extensive literature review, this is the first documented case of triple synchronous tumors with a combination of BCC of the right nasolabial area, PTC and prolactinoma in local, national and international studies. Double primary tumors are rare with a prevalence rate of 3-5%. Triple primary tumors are even rarer having an occurrence of 0.5%. CONCLUSION Accurate knowledge on disease prevalence, pathophysiology and symptomatology correlated with guided history taking and astute physical examination is very important in rare medical conditions and complicated cases. Extensive work up based on sound clinical knowledge and judgement aids also in answering clinical questions encountered in a diagnostic dilemma.